Volatility Spillovers and Dynamic Correlations among Foreign Exchange Rates and Bond Markets of Emerging Economies - Aydemir, Resul; Guloglu, Bulent; Saridogan, Ercan (Panoeconomicus, 2019)
In this paper, we first examine how important historical shocks during and after the 2007-2008 global financial crisis affect the size and the persistence of volatilities among exchange rates and the ten-year bond rates of the Fragile Five countries (i.e., Brazil, India, Indonesia, South Africa and Turkey). We then investigate separately the dynamic interactions between exchange rates and the ten-year bond rates of the Fragile Five. We utilize a multivariate GARCH model (FIAPARCH-DCC model) and volatility impulse response functions to achieve these objectives. The results suggest that shocks’ positive impacts on expected conditional variances of the variables are largely market-specific and different. Shocks have a more significant impact on bond markets than on foreign exchange markets. We also find that the dynamic conditional correlation series of bonds exhibit much lower correlations than those associated with exchange rate returns.Keywords: Volatility spillovers, Exchange rates, Interest rates, Dynamic correlations, Emerging markets. JEL: C32, F31, G12, G15.